Testing the initial conditions and dynamical evolution of star clusters using Gaia- I - Allison, Richard James (Monthly notices of the Royal Astronomical Society, 2012)
We investigate how the properties of escaping stars are related to the initial conditions of their birth clusters. We find that the number of escaping stars, their spatial distribution and their kinematics show a dependence on the initial conditions of the host cluster (substructure and virial ratio). Thus the properties of escaping stars can be used to inform us of the initial conditions of star formation, and also provide a window into the dynamical history of star clusters. The European Space Agency’s Gaia mission will make observations of the positions and proper motions of these escaping stars at the required accuracy to allow us to investigate the dynamical evolution of local star clusters and provide an important insight into the initial conditions of star formation.